Impact of roughage-concentrate ratio on the water footprints of beef feedlots. (July 2017) - Palhares, Julio Cesar Pascale; Morelli, Marcela; Junior, Ciniro Costa
Abstract: The aim of this study was to determine the water footprint of beef feedlots up to the farm gate and evaluate the impact of roughage-concentrate ratio on the green water footprint. The study purpose was to provide strategic insights about nutritional management and water used that have a positive impact reducing water demand and increasing water efficiency. A regional bottom-up approach of the beef feedlot production was applied and water footprint methodology was used as the primary method. We included green and blue volumetric water footprint. Sensitivity assessment was done to explore differences in agricultural performance. Total water footprint ranged from 1935 to 9673 m 3  kg − 1 of meat. The results are demonstrating the variability in water footprint that can exist from farm to farm. Green water represented on average 84.5% and blue water 15.4% of the footprint value. The farms with larger amounts of concentrate in the diet had high footprint values and the differences in feed composition have a significant effect on the water footprint. The average water footprint of the current crop yield was 5814 L kg − 1 of meat. With a reduction of 25% in the current crop yields, it was 7.416 L kg − 1 of meat and with an increase of 25% in the current crop yields, 4677 L kg − 1 of meat. These results show that increasing agricultural productivity has positive impacts on reducing the water footprint. The results show that the water footprint values of feedlots are determined largely by the type of animal diet and by performance indicators of the animals. The roughage-concentrate ratio and type of roughage are the nutritional aspects that most significantly influence the footprint values. This study supports the recommendation that beef feedlots should place emphasis on maximizing the use of roughage, because this could decrease the pressure on fresh water resources. Highlights: We should reduce the risks associated with animal water demand. Provide insights about cattle nutritional management and water used. Hydro-efficiency in livestock depends on agriculture. Farms with larger amounts of concentrate in the diet has high footprint values. Water footprints are determined by animal diet and animal performance.